Level measurement, regional variations, and the dynamic evolution of active aging in China—analysis based on CHARLS tracking data - Jiru Guo; Xiaoli Zhang; Xiaoli Zhang; Longyin Chen; Hong Yang (Frontiers in Public Health)
IntroductionGiven the world’s largest and increasingly serious aging population, China has elevated “positively responding to aging of population” to a national strategy. Exploring the current state and evolutionary trends of active aging over the past decade is a fundamental prerequisite and the primary task for implementing this strategy.MethodsBased on data from the China Health and Retirement Longitudinal Study (2011-2018), this study primarily employs methods such as the entropy method, Gini coefficient, Moran index, and Kernel density estimation to analyze the development level, regional differences, and dynamic evolution of active aging in China.Results(1) From a general point of view, the overall level of active aging in China has not been high in the past decade, but has shown a rising trend year by year. Older Chinese people exhibit high levels of physical and mental health, but social participation and economic status remain areas of weakness in active aging. (2) Inter-regional differences are the main source of the overall differences in the level of active aging in China. (3) There is a spatial clustering of the active aging level in China, along with a neighborhood effect. (4) The bifurcation phenomenon of active aging in China has intensified over time. While the eastern region exhibits uneven development, the central and western regions have generally had more balanced growth.DiscussionTo improve the level of active aging among older adult individuals in China, policymakers should continuously optimize policies and pay more attention to the economic status and social participation of the older adult. Local governments should not only fully leverage their regional advantages but also interact with other regions to achieve cross-regional joint development.